Elhamma Walker (Lepidoptera: Hepialidae) revisited: adult morphology, assessment of recently proposed synonyms and descriptions of two species - Simonsen, Thomas J. (Zootaxa, 2015)
I revise the Australian-New Guinean ghost moth genus Elhamma. Two recent synonymies are assessed, and two new species from New Guinea, E. grehani sp. nov. and E. viettei sp. nov. are described. I provide an updated diagnosis for the genus and conclude that the presence of only 2 M-veins in the hind wing in both sexes (when females are known) and a strongly cup-shape juxta in the male genitalia are unique diagnostic characters among Hepialidae. I give a detailed description of the adult morphology based on male E. australasiae, and provide a key to all known species based on adult male characters.